Isolated Otolith Dysfunction in Persistent Postural-Perceptual Dizziness - Murofushi, Toshihisa; Nishimura, Koji; Tsubota, Masahito (Frontiers in Neurology, 2022)
The aims of this study were to investigate otolith dysfunction, especially isolated otolith dysfunction (with preserved semicircular canal function) in persistent postural-perceptual dizziness (PPPD) patients. Twenty-one patients who had been diagnosed with PPPD were enrolled in this study. The subjects filled out questionnaires (the Dizziness Handicap Inventory [DHI] and the Niigata PPPD Questionnaire [NPQ]) and underwent vestibular evoked myogenic potential (VEMP) tests, video head-impulse tests (vHIT), and stabilometry. Among the 21 subjects with PPPD, 9 showed isolated otolith dysfunction, 4 exhibited both otolith dysfunction and semicircular canal dysfunction, and 2 demonstrated isolated semicircular canal dysfunction. Six subjects exhibited normal VEMP and vHIT results. Concerning the subjects’ questionnaire scores and stabilometric parameters, there were no significant differences among subgroups when the subjects were classified according to their VEMP and vHIT results while stabilometric parameters obtained in PPPD subjects were significantly increased than published data of healthy subjects. As precipitating conditions for PPPD, vestibular neuritis was the most frequent and the second most was idiopathic otolithic vertigo. In conclusion, the majority of PPPD patients had otolith dysfunction, and most of them showed isolated otolith dysfunction. Idiopathic otolithic vertigo can be a precipitating factor of PPPD. While otolith dysfunction may be associated with initiation of PPPD symptoms, PPPD symptoms are also considered to be associated with other dysfunctions of the sensory processing system.